An experimental study on foamed concrete foundation as peat soil replacement in sarawak - Lai, Phui Hua (Universiti Malaysia Sarawak (UNIMAS), 2011)
This research is concerned with the prospects of using foamed concrete as fill material (which will be referred as foamed concrete foundation in subsequent sections) on peat land based on the density replacement method. This study adopted the concept of "floating foundation" where the density of foamed concrete foundation shall be less than or equal to the density of excavated peat soil. Two (2) mix proportions offoamed concrete were compared in this study. Although the strength of foamed concrete is not the main focus in this study, the target strength value should not be less than 8 MP~Assumptions made in the experiments are: -(a) The peat land is fully saturated, (b) Depth of the peat soil layer is 5 -10m, (c) The depth of groundwater table is 0 -40 cm. Two major findings of this study are: -(i) the physical properties and characteristics of foamed concrete make it suitable for peat replacement. The density of the foamed concrete ranged from 600 1m3 to 1200 kg/m3• The relationship between fresh and harden densities, the deformation of foamed concrete, and the percentage of the void of foamed concrete was investigated. (ii) The feasibility study of foamed concrete foundation: -shape, settlement and stability; it was expected that the foamed concrete shape would alter the stability and the initial settlement of the foamed concrete foundation. This study confirmed the suitability of foamed concrete foundation as peat soil replacement with load carrying capacity by controlling the density and the shape of the foamed concrete foundation.